2020
DOI: 10.1097/ico.0000000000002339
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Central Corneal Thickness in Cross-Linked Keratoconic Eyes

Abstract: Purpose: To compare the central corneal thickness (CCT) measurements measured by using the Pentacam Scheimpflug system with the CCT measured using ultrasound pachymetry (UP) and to compare the compatibility between the methods in normal, keratoconic, and cross-linked keratoconic corneas. Methods: The study included 50 eyes of 50 patients with keratoconus (keratoconus group), 50 eyes of 50 patients with progressive keratoconus who underwent corneal cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Corneal thickness was measured thinner in the cross-linked group than in the progressive uncross-linked group despite a atter anterior surface. In a recent study by the current authors, the CCT measurement difference between the Pentacam and ultrasound pachymetry was largest in the CCL group, followed by the keratoconus and control groups (-20.9 ± 21.5, -10.6 ± 20.3, and 0.4 ± 6.8 µm), and it was concluded that pachymetric measurements from Scheimp ug must be interpreted with extreme caution [19].…”
Section: Discussionmentioning
confidence: 61%
“…Corneal thickness was measured thinner in the cross-linked group than in the progressive uncross-linked group despite a atter anterior surface. In a recent study by the current authors, the CCT measurement difference between the Pentacam and ultrasound pachymetry was largest in the CCL group, followed by the keratoconus and control groups (-20.9 ± 21.5, -10.6 ± 20.3, and 0.4 ± 6.8 µm), and it was concluded that pachymetric measurements from Scheimp ug must be interpreted with extreme caution [19].…”
Section: Discussionmentioning
confidence: 61%
“…The physiology of this corneal thinning after CCL still not identi ed: however, structural changes occur in corneal collagen brils (28), such as changes in corneal hydration (29), compression of collagen brils (30), edema (31), and keratocyte apoptosis (31) are discussed in the literature. It should be borne in mind that previous studies have that due to the difference between the Pentacam and ultrasound pachymetry, pachymetric values obtained from Pentacam printout should be interpreted with extreme discretion (32).…”
Section: Discussionmentioning
confidence: 99%
“…The physiology of this corneal thinning after CCL is still not identi ed: however, structural changes occur in corneal collagen brils (28), such as changes in corneal hydration (29), compression of collagen brils (30), edema (31), and keratocyte apoptosis (31) are discussed in the literature. It should be borne in mind that previous studies have shown that due to the difference between the Pentacam and ultrasound pachymetry, pachymetric values obtained from Pentacam printout should be interpreted with extreme discretion (32).…”
Section: Discussionmentioning
confidence: 99%